Peningkatan Ekonomi Desa melalui Pariwisata: Memahami Regulasi dan Manfaatnya - Febriani, Dita; Pebiyan, Anggita; Ali. A, Muh. Daud; Violeta, Fadinda Rishtey; Kalina. L, Ratu Putria (Jurnal Pengabdian Nasional (JPN) Indonesia, 2024)
The Smart Village program aims to enhance community welfare through the application of technology and innovation. In Curahdami village, low literacy and competency levels, particularly among ex-ODGJ (people with mental disorders), are due to low productivity and insufficient skill development support. Social stigma, lack of motivation, and minimal family attention exacerbate this situation, while social disparities limit access to essential services. To address these issues, an empowerment program for ex-ODGJ was designed through the "Rumah Kreasi Budaya Desa," a center for developing creative products based on local wisdom. The program seeks to enhance artistic skills and market creative products to support the growth of the creative industry and create new jobs. This research employs a participatory-action approach, engaging the community in the planning, implementation, and evaluation of the program. Data collection methods included participatory observation, in-depth interviews, and documentation of activities. From June to August 2024, the program targeted 40 beneficiaries, including 35 ex-ODGJ from several villages and some individuals with disabilities. Of these, 62.5% showed significant improvement in artistic skills, while 37.5% demonstrated increased interest in creative activities. Nevertheless, challenges such as limited resources, low community capacity, and insufficient policy support persist. Therefore, it is crucial to improve human resource capacity, develop strategic partnerships, and strengthen stakeholder support to ensure the program's success